A Pilot Study of the Humoral Response Against the AntiSense Protein (ASP) in HIV-1-Infected Patients - Savoret, Juliette; Chazal, Nathalie; Moles, Jean-Pierre; Tuaillon, Edouard; Boufassa, Faroudy; Meyer, Laurence; Lecuroux, Camille; Lambotte, Olivier; Van De Perre, Philippe; Mesnard, Jean-Michel; Gross, Antoine (Frontiers in Microbiology, 2020)
The existence of an antisense Open Reading Frame (ORF) that encodes a putative AntiSense Protein (ASP) on the proviral genome of HIV-1 was a source of debate for 30 years. During the last years, some progresses have been made to characterize the cellular immune response against ASP in HIV-1 seropositive patients. However, no tools were available for the detection of antibodies to ASP in the plasma of HIV-1-infected patients during the natural course of the infection. The aim of our study was to develop a Luciferase Immuno-Precipitation System (LIPS) to monitor the quantitative detection of ASP-specific antibodies in the plasma of HIV-1-infected patients (antiretroviral therapy (ART) naive-patients, patients under ART and HIV-1 controllers). We further used this approach to delineate the epitopes of ASP targeted by antibodies. Antibodies directed against ASP were detected in 3 out of 19 patients who discontinued ARV (15%) and in 1 out of 10 ART-naive patients (10%), but were neither detected in HIV-1 infected patients under ART nor in HIV-1 controllers. Individual variations in levels of ASP-specific antibodies were detected overtime. Both the conserved prolin-rich motif and the core 60-189 region of ASP were found to be essential for antibody recognition in the 4 patients tested positive for anti-ASP antibodies, who were all untreated at the time of sampling. Moreover, for 2 of these patients, increased levels of ASP-specific antibodies were observed concomitantly to viremia declines. Overall, our method may represent a useful tool to detect a humoral response to ASP in HIV-1-infected patients, which allowed us to confirm the expression of ASP during the course of HIV-1 infection. Further studies will be needed to fully characterize the humoral response to ASP in HIV-1-infected patients.